The Freer the Fatter? A Panel Study of the Relationship between Body-Mass Index and Economic Freedom - Åsa Ljungvall (Lund University, School of Economics and Management, Department of Economics, 2013)
Along with the economic and technological developments of the past decades, obesity has become a growing public health problem. This study empirically investigates whether the large and widespread increases in body-mass index (BMI) that have been observed around the world are related to economic freedom, as measured and defined by the Economic Freedom of the World Index. Economic freedom is part of the environment in which individuals make choices about food intake and physical activity, and may encourage unhealthy behavior and affect body weight by changing the opportunity sets. It may for example affect the quality and quantity of foods available to consumers, the access to safety nets, and the access to environments for physical activity. The empirical analysis is based on a panel of 31 high-income countries and data for the period 1983 to 2008. It finds a positive and statistically significant relationship between the level of economic freedom and both the level of, and five-year change in, BMI. Decomposing the freedom index into sub-indices measuring economic freedom in five sub-areas (government, legal structure, sound money, trade, and regulations) shows that freedom in the regulations dimension is the most consistent contributor to this result.
Keywords: I10; I12; I15; I18; O11; P10; 330; body-mass index; obesity; economic freedom; economic freedom of the world index; health production; panel